197k views
0 votes
Solve (x + 3)^2 – 5 = 0 using the quadratic formula.

Solve (x + 3)^2 – 5 = 0 using the quadratic formula.-example-1
User Micki
by
4.9k points

1 Answer

4 votes

Okay, here we have this:

Considering the provided equation, we are going to solve it using the quadratic formula, so we obtain the following:


\begin{gathered} \mleft(x+3\mright)^2-5=0 \\ x^2+6x+9-5=0 \\ x^2+6x+4=0 \\ x_(1,\: 2)=(-6\pm√(6^2-4\cdot\:1\cdot\:4))/(2\cdot\:1) \\ x_(1,\: 2)=(-6\pm\:2√(5))/(2\cdot\:1) \\ x_1=(-6+2√(5))/(2\cdot\:1),\: x_2=(-6-2√(5))/(2\cdot\:1) \\ x=-3+√(5),\: x=-3-√(5) \end{gathered}

Finally we obtain that the correct answer is the option A.

User Divesh Premdeep
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.